Growth Breaks and Growth Spells in Sub-Saharan Africa - Arizala, Francisco (IMF Working Papers; Working Paper ;, 2017)
This paper examines the growth performance of sub-Saharan African countries since 1960 through the lens of growth turning points (accelerations and decelerations) and periods of sustained growth (growth spells). Growth accelerations are generally associated with improved external conditions, increased investment and trade openness, declines in inflation, better fiscal balances, and improvements in the institutional environment. Transitioning from growth accelerations to growth spells often requires additional efforts beyond what is needed to trigger an acceleration. Growth spells are sustained by fiscal policy that prevents excessive public debt accumulation, monetary policy geared toward low inflation, outward-oriented trade policies, and structural policies that reduce market distortions, as well as supportive external environment and improvements in democratic institutions. Overall, determinants of growth spells in sub-Saharan Africa are different from those in the rest of the emerging and developing countries.